ANALISIS DATA DALAM RANCANGAN PENELITIAN KUALITATIF - SUYITNO (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2020)
The design of a study is a very important and major problem in a study. The skill to compose a research design is a problem that is absolutely necessary for a researcher. The skill of drafting begins with understanding the various rules in it. That is because of how important research design is to one's success in carrying out the qualitative research process. Furthermore, the research design is different from the research report, but in its application, the research report sometimes is quoted from the research design. A good qualitative research design will be able to provide an initial overview of the research process. Thus, the research design serves as a smooth implementation of research to be conducted by researchers. The several design functions of a study include the following: 1) providing directions for answering a research question; 2) determine the restrictions on activities in accordance with the focus of the research; 3) allows researchers to avoid the emergence of various problems in the middle of the research process.